Diagnostic value of magnetic resonance imaging ectopic posterior pituitary hyperintense signal in pituitary macroadenoma - Luo, Yi-Lin; Gu, Fang; Fan, Hai-Qing; Du, Jin-Hui; Yu, Yue; Liu, Li-Kun; Liao, Xin (Frontiers in Oncology, 2022)
Objective: When the lesions in the sellar region are large, they can involve both the inside and outside the sella, which brings challenges to the differential diagnosis of pituitary macroadenoma and lesions other than macroadenoma. Therefore, this study explored the diagnostic value of an ectopic posterior pituitary hyperintense signal (EPPHS) in pituitary macroadenoma and its possible causes. Methods: The clinical and imaging data of 131 patients with sellar tumors or tumor-like lesions involving both intrasellar and extrasellar regions in the Affiliated Hospital of Guizhou Medical University from February 2011 to December 2021 were analyzed retrospectively. The diagnostic value of EPPHS in pituitary macroadenoma was analyzed. The differences in clinical and imaging indexes between the EPPHS-positive group and the EPPHS-negative group were compared. Results: These 131 cases of sellar tumors or tumor-like lesions involving both intrasellar and extrasellar regions included 91 cases of pituitary macroadenoma and 40 cases of lesions other than macroadenoma or simply other lesions. The receiver operator characteristic curve analysis suggested that EPPHS had a diagnostic value in diagnosing pituitary macroadenoma (area under the curve = 0.857, P = 0.0001). Compared with the EPPHS negative group, the median prolactin level in the EPPHS positive group was significantly higher (P < 0.05). Through ROC curve analysis, prolactin value was found to be of diagnostic value for EPPHS (AUC=0.612, P=0.0312). Conclusion: In sellar tumors or tumor-like lesions involving both intrasellar and extrasellar regions, the appearance of EPPHS is helpful in the diagnosis of pituitary macroadenoma. The formation of EPPHS may be related to injuries to the pituitary stalk.